The Identification of House Characteristic in the Karang Mumus River Bank Settlement Samarinda City Based on Settlement Development Patterns - Adventsa Novitasari; Edward E. Pandelaki (PT FORMOSA CENDEKIA GLOBAL, 2023)
An Living in the river region has certain characteristics and uniqueness, as the body of a house is familiar with the situation and area of the bengals. The island of Kalimantan is divided by bengals-large, characteristic and characteristic areas and other areas, one of which is the sharpening child of the master river that divides the city of Samarinda. The typology of the house of the Karang Mumus river comprises three types of structures that were built on the river's edge or commonly called floating houses, and those on the waterfront or transitional zone between the water and the land commonly called stilts, and the buildings on the ground. The research method used by the writer is the qualitative descriptive method of identifying house typology above the river Karang Mumus to evaluate whether it measures up to the standards associated with the settlements above the river. The purpose of this article was to find typology of the buildings at the settlement of the Karang Mumus river situated on the flotation segment, stage, and concrete. In addition to the configuration of forms and Spaces, it is acquired a developmental pattern that can have an impact on the characteristics of the settlement